(untitled) (Research, Society and Development, 2023)
Aromatherapy is the art and science that aims to provide health and well-being of the body, mind and emotions, through the therapeutic use of essential oils. Few studies are related to the use of Lavender essential oil during pregnancy, with it being more cited in research on pain during labor. The objectives were to investigate the contributions of lavender essential oil in reducing discomforts related to the gestational period, verify pregnant women’s knowledge about aromatherapy and identify the main discomforts pertinent to the pregnancy state for which the participants identified contributions of aromatherapy. This is a descriptive, qualitative intervention research that was initially carried out with four pregnant women and concluded with just one, all registered in a Family Health Strategy in a city in the northwest region of Rio Grande do Sul. The data were collected through a form-guided interview and analyzed through analysis of the content of the statements. Aromatherapy brought positive results for pregnant women in their well-being, suggesting that it is an effective non-pharmacological option for discomforts related to the gestational period. The need to carry out more studies on the topic and the importance of continuing health education to expand the supply of integrative and complementary health practices is highlighted.